Implementation of promotion strategy and quality of service to PT. Batam Indah Tour & Travel through social media - Golan Hasan; Winson Leon (Universitas Internasional Batam, 2023)
In recent years we have been hit by the Covid-19 virus pandemic which has had a very big impact on all industries in the world, especially in the tourism industry. The purpose of this activity is to increase sales and increase tourism in the city of Batam especially to PT. Batam Indah Tour & Travel. due to the impact of the Covid-19 virus, which has caused many people not to dare to travel on vacation. This activity is carried out by making tourism posters to be published on social media such as Instagram. Thus the authors hope to help company owners to increase sales of holiday packages and increase Batam city tourism. The author collects data by visiting the company and conducting interviews or debriefings with the company owner.